Primerjalni narečni strokovni (slikovni) slovar za besedje s tematskega področja vrt in sadovnjak v izbranih govorih panonske in koroške narečne skupine - Koletnik, Mihaela (Jezikoslovni zapiski, 2011)
This article presents vocabulary connected with gardens and orchards in the form of a comparative dialect dictionary. The comparison is made based on a sample of selected subdialects of the Carinthian and Pannonian dialect groups, which are not geographically adjacent. All dialect dictionaries published until now (there are around 30) are restricted to a speech of one particular place (town) or region. So far Slovenes have no comparative technical (picture) dialect dictionary. Such a work is therefore a pioneer among Slovene dialect dictionaries.
Keywords: Carinthian dialect; comparative technical dialect dictionary; dialect lexicography; dialectal dictionaries; dialectology; dialektologija; koroško narečje; Prekmurian; Prekmurje dialect; prekmursko narečje; primerjalni narečni slovarji; Slovene; Slovene dialects; Slovene language; slovenska narečja; slovenščina; strokovni slovarji